2020
DOI: 10.5539/elt.v13n11p140
|View full text |Cite
|
Sign up to set email alerts
|

Internally Displaced and Refugee Students in Cameroon: Some Pedagogical Proposals

Abstract: For some six years now, Cameroon has been experiencing unprecedented war disturbances. Since 2014, its three northern regions have been undergoing the hardship of Boko Haram ruthless attacks leading to thousands of internally and externally displaced families and hundreds of schools closed down. The Minawao Refugees Camp near Mokolo with over 60 000 inhabitants, mostly Nigerians, somewhat testifies to the gravity of the situation. A similar Camp is located in Gado-Badzere near Garoua-Boulaï in the Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…But the current educational programmes do not enable this. New programmes need to be designed in clear language and with clear curricula and objectives (see Safotso, 2020). This can effectively work only if all the stakeholders work hand in hand through nationwide discussions on the issue.…”
Section: Use Of Appropriate Languagementioning
confidence: 99%
“…But the current educational programmes do not enable this. New programmes need to be designed in clear language and with clear curricula and objectives (see Safotso, 2020). This can effectively work only if all the stakeholders work hand in hand through nationwide discussions on the issue.…”
Section: Use Of Appropriate Languagementioning
confidence: 99%
“…However, few studies on refugee education focus on teachers and their experiences, which affect their teaching competencies and personality. Previous studies researching teachers' perspectives found that teachers are dissatisfied with their teacher training prior to the start of their position (Bodon & Votteler, 2017;Safotso, 2020;Simopoulos & Magos, 2020). Research conducted by Anastasia Papapostolou, Polyxeni Manoli and Anna Mouti (2020) revealed how teachers experience anxiety and challenges, mainly due to their lack of training in intercultural education.…”
Section: Introductionmentioning
confidence: 99%